2018
DOI: 10.3389/fmed.2018.00210
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Singleton Pregnancies From Restorative Reproductive Medicine (RRM) After Failed IVF

Abstract: Objectives: To determine the live birth rate for patients who chose to undergo treatment with Restorative Reproductive Medicine (RRM) after previous IVF (includes ICSI). To look at birth outcomes with RRM after IVF, particularly rates of twin and higher order pregnancies, premature birth, low birth weight, and potential cost savings achieved with RRM.Setting: Two outpatient clinics in Ireland providing advanced RRM treatment of infertility.Materials and methods: All patients presenting between January 2004 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 28 publications
3
19
0
7
Order By: Relevance
“…Still, there are few reports on an outcome of spontaneous conception after reproductive surgery due to an opinion that reproductive surgery should only be performed as an initial part of infertility treatment before proceeding to IVF/ICSI 9 . Nevertheless, encouraging reports on a high spontaneous pregnancy rate after reproductive surgery, as in this study, emerged in the last years 8,10 . Similar to our finding, Boyle et al 8 have found the low preterm delivery rate in women who conceived spontaneously after restorative reproductive medicine after failed IVF.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Still, there are few reports on an outcome of spontaneous conception after reproductive surgery due to an opinion that reproductive surgery should only be performed as an initial part of infertility treatment before proceeding to IVF/ICSI 9 . Nevertheless, encouraging reports on a high spontaneous pregnancy rate after reproductive surgery, as in this study, emerged in the last years 8,10 . Similar to our finding, Boyle et al 8 have found the low preterm delivery rate in women who conceived spontaneously after restorative reproductive medicine after failed IVF.…”
Section: Discussionsupporting
confidence: 54%
“…Nevertheless, encouraging reports on a high spontaneous pregnancy rate after reproductive surgery, as in this study, emerged in the last years 8,10 . Similar to our finding, Boyle et al 8 have found the low preterm delivery rate in women who conceived spontaneously after restorative reproductive medicine after failed IVF. Indeed, waiting for spontaneous conception in infertile women who are often at advanced reproductive age is discouraging.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Many studies have confirmed that a single administration of GnRH-a can enhance the clinical outcomes of IVF-ET treatment. 6,8,9,14 Administration of multiple boluses of GnRH-a in LPS protocols has become more common. Pirard et al.…”
Section: Discussionmentioning
confidence: 99%